Comparative in vitro and in vivo evaluation of matrix, osmotic matrix, and osmotic pump tablets for controlled delivery of diclofenac sodium - Rani, M.; Mishra, B. (AAPS PharmSci Editorial Office, 2004)
The aim of this investigation was preparation and comparative evaluation of fabricated matrix (FM), osmotic matrix (OM), and osmotic pump (OP) tablets for controlled delivery of diclofenac sodium (DS). All formulations were evaluated for various physical parameters, and in vitro studies were performed on USP 24 dissolution apparatus II in pH 7.4 buffer and distilled water. In vivo studies were performed in 6 healthy human volunteers; the drug was assayed in plasma using HPLC, and results were compared with the performance of 2 commercial tablets of DS. Various pharmacokinetic parameters (ie, Cmax, Tmax, area under the curve [AUC0-24], and mean residence time) and relative bioavailability were compared. All fabricated formulations showed more prolonged and controlled DS release compared with commercial tablets studied. The OM and OP tablets, however, performed better than the matrix tablets. The rate and extent of drug release from FM1 matrix tablets (single polymer) was significantly different from that of FM2 (admixed polymers). Type of porosigenic agents and osmogens also influenced the drug release. Analysis of in vitro data by regression coefficient analysis revealed zero-order release kinetics for OM and OP tablets, while FM tablets exhibited Higuchi kinetics. In vivo results indicated prolonged blood levels with delayed peak and improved bioavailability for fabricated tablets compared to commercial tablets. It was concluded that the osmotic matrix and osmotic pump tablets could provide more prolonged, controlled, and gastrointestinal environmental-independent DS release that may result in an improved therapeutic efficacy and patient compliance
Keywords: Controlled release; Diclofenac sodium; Matrix tablets; Osmotic matrix tablets; Osmotic pump tablets